The Role of Framing Effect and Social Value Orientation in Cooperation in Repeated Social Dilemmas - Grežo, Matúš; Pilárik, Ľubor (Psykhe, 2023)
The research in the area of framing effect has thoroughly addressed the question whether individuals cooperate more in negatively framed situations than in positively framed situations. However, so far, the studies brought inconsistent results. In the present study, it is hypothesized that the effect of framing on cooperative behavior depends on person's social value orientation. 79 Slovak university students (19 men, 60 women) divided into five small social groups were presented with a decomposed game to measure their social value orientation. Then, they cooperated in 9 repeated decisions within 2 different social dilemmas about the distribution of the financial resources. After each decision, either negatively or positively framed information was provided about how the groups' financial resources were affected. The results of the semi-robust two-way MANOVA showed that framing effect did not significantly affect cooperation, but social value orientation did. Importantly, social value orientation did not moderate the effect of framing on cooperation. The findings indicate the need for further examination of other possible factors, such as emotions, that may moderate or mediate the effect of framing on cooperation.